Real-world prognostic factors for first-line EGFR-TKI efficacy in advanced NSCLC patients harboring EGFR 21 L858R mutation - Yan’e Liu; Lu Chen; Xin Zhu; Hua Zhang; Baoshan Cao (Global Medical Genetics)
Objective: This study aimed to investigate the prognostic factors for the treatment efficacy of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) in non-small cell lung cancer (NSCLC) patients with EGFR exon 21 L858R mutation. Methods: The study enrolled patients with advanced EGFR L858R-mutant NSCLC who received first-line EGFR-TKI treatment between January 2019 and April 2024. Cox regression analyses were performed to identify the prognostic factors from clinical characteristics and concomitant genetic alterations that influenced progression-free survival (PFS) and overall survival (OS). Results: According to the study of a cohort of 120 patients, we found that more metastatic organs (≥3 organs), specific metastatic patterns (liver and bone involvement), concurrent TP53 mutations, and worse Eastern Cooperative Oncology Group Performance Status (ECOG PS) were associated with shorter PFS. And ECOG PS was an independent predictive factor for PFS. Similarly, metastatic organs ≥ 3 (HR, 2.719; 95 % CI, 1.386–5.333; p = 0.004), ECOG PS of 2 (HR, 10.756; 95 % CI, 4.002–28.906; p < 0.001), and body mass index (BMI)＞24 kg/m2 (HR, 0.335; 95 % CI, 0.147–0.760; p = 0.009) were associated with worse OS. We also observed that patients harboring TP53 co-mutations demonstrated significantly inferior PFS compared with their TP53 wild-type counterparts (13.7 months vs. 18.8 months; p = 0.006). Conclusions: This study identified several factors significantly associated with worse response to EGFR-TKIs in NSCLC patients with EGFR L858R mutation and respective independent predictive factors for PFS and OS. These findings could enable personalized therapeutic efficacy assessment to facilitate clinical decision-making for EGFR L858R-mutant NSCLC patients treated with EGFR-TKIs.